Adaptive and inclusive seating design for transit-oriented interior - Brisbhanuharto, Muhammad Daffa; Primayudha, Novrizal (ARSNET, 2025)
As transit-oriented interiors increasingly evolve into complex commercial and social micro-environments and serve diverse user groups, seating design must respond beyond basic functionality to address the need for adaptation and inclusivity. This study explores adaptive and inclusive design strategies through the development of seating design in such a context. This research follows Liedtka's human-centred, iterative design process comprising stages such as empathy, definition, ideation, and prototyping in developing seating design for a transit-oriented interior at Canabeans Coffee, located within KCIC Halim High-Speed Rail Station, Jakarta. The design integrates ergonomic, aesthetic, and accessibility considerations while responding to contextual challenges of a high-density transit environment. The design study proposes a circular bench as a form of seating that promotes adaptation and inclusivity for such a context. The bench is conceived as a seating solution that gives a moment of pause for its users in navigating the interior. The circular arrangements are adaptable for various user needs, fostering social interaction. The proportion, details, and materials of the bench support various mobility needs and enhance their spatial experience. This study contributes to the discourse on adaptive and inclusive strategies in public furniture design, emphasising the importance of harmonising function, comfort, and social meaning in transit-oriented interiors.